Risk Identification in Sports Organization - Maria Hudakova; Katarina Buganova; Maria Luskova (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
As the COVID-19 pandemic enters its third year and the economy continues to recover, it is clear that today's dynamic, unpredictable risk environment will remain. Due to the influence of other unexpected and changing sources of risks from the external and internal environment, situations arise that affect the fulfillment of set goals and the effectiveness of decision-making processes. This uncertainty underlines the need for prevention and the importance of risk management in sports organizations so that organizations can better prepare for potential crises. While in some countries (e.g., the USA, Australia, and others), it is common for the management of a sports organization to be aware of its serious (key) risks, this is not the case in Slovakia. The contribution aims to present the basic concept of risk identification for sports organizations to support sustainability resulting from the current requirements of practice in Slovakia and respect for world trends. The proposed concept's essence is identifying risks in connection with the application and significance of selected methods and techniques of risk identification. The proposed concept should focus on strategic management and establish responsibility for identifying risks to minimize the risks' negative impact. The benefit of the contribution is the strengthening of support for the application of risk management in sports organizations not only in Slovakia but also in neighboring countries. With a proper understanding and effective management of risks within processes and functions, sports organizations can anticipate emerging risks and increase the probability of achieving the goals of profit and sports success.
Keywords: Z2; Z23; Z28; Z29; 330; risk; risk manager; risk identification; methods and techniques of risk management; sports organization